Hierarchical porous carbon material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611116878.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]传统气体活化受限于表层浅活性化的问题:传统气体活化过程多在独立碳化阶段完成后进行
本发明通过“前置结构稳定化辅助内部气相刻蚀”的协同构筑策略,实现了对生物质热解收缩行为、内部传质路径及气-固相活化过程的协同调控,从而有效抑制高温热解过程中的结构致密化与孔道塌陷,促进活化气体向碳骨架内部均匀扩散与刻蚀,最终构建具有连续离子传输通道的分级孔结构;相比现有技术,本发明具有以下优点:
Smart Images

Figure CN122916136A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of biomass carbon materials and electrochemical energy storage technology, and more specifically, to a hierarchical porous carbon material, its preparation method, and its application. Background Technology
[0002] With the transformation of the global energy structure, electric vehicles, portable smart devices, and large-scale smart grids are placing increasingly stringent demands on efficient energy storage devices. Among numerous energy storage devices, supercapacitors and novel hybrid capacitors have become a research hotspot in the current new energy field due to their combination of the high energy density of traditional secondary batteries and the high power density and ultra-long cycle life of electrochemical capacitors. The core factor determining the energy storage performance of such capacitors lies in the electrode materials. Porous carbon materials, with their extremely high specific surface area, excellent conductivity, highly tunable pore network, and outstanding physicochemical stability, can provide abundant double-layer charge adsorption sites and rapid ion transport channels, and are widely recognized as the capacitor electrode materials with the greatest commercial application potential.
[0003] Currently, the main methods for preparing porous carbon materials include physical activation, chemical activation, and template methods. While chemical activation methods using KOH and NaOH can achieve high specific surface areas, their activation process is highly corrosive, easily leading to over-etching of the carbon framework and structural pulverization. Furthermore, the post-processing is complex and generates significant wastewater discharge, hindering green, large-scale preparation. In contrast, gas activation methods, represented by CO2 or water vapor, are typical physical activation methods. They use high-temperature gas-solid reactions to perform relatively gentle etching of the carbon framework, offering advantages such as uniform etching, environmental friendliness, and better preservation of the carbon framework's integrity. Therefore, they have gradually become an important research direction for biomass porous carbon in recent years.
[0004] The preparation of biomass-based carbon materials generally involves the high-temperature pyrolysis of biomass into carbon. However, since biomass is mainly composed of cellulose, hemicellulose, and lignin, its internal structure relies primarily on a natural hydrogen bond network for stability. During direct high-temperature pyrolysis, as the temperature rises, dehydration and weakening of hydrogen bonds occur first within the biomass, followed by chain breakage, volatile matter release, and aromatization rearrangement. As the original hydrogen bond-supported structure gradually destabilizes and the stable carbon skeleton is not yet fully formed, the material is prone to significant thermal shrinkage and structural collapse under thermal stress, leading to problems such as closure of natural pores, decreased mesoporous connectivity, and increased internal mass transfer resistance.
[0005] Typically, traditional gas activation is performed after carbonization. However, carbon materials undergo significant densification after pyrolysis due to their dense structure and the collapse of pores during the high-temperature process. This makes it difficult for the activation gas to penetrate further into the carbon skeleton, and it can only perform limited etching in the surface area. Therefore, it is difficult to form a uniform, through-hole hierarchical pore structure.
[0006] Existing biomass porous carbon preparation technologies still face numerous challenges in terms of pyrolysis stability, activation uniformity, and pore structure control. These challenges significantly limit the ion transport efficiency, rate performance, and power output of the resulting materials, as detailed below:
[0007] Structural thermal instability and collapse during high-temperature pyrolysis: During high-temperature pyrolysis, the natural hydrogen bond network within biomass gradually weakens due to dehydration and increased thermal motion. Subsequently, cellulose, hemicellulose, and lignin undergo further chain breakage, volatile matter release, and aromatization rearrangement. Because the original hydrogen bond support structure has become unstable, and a stable carbon skeleton has not yet been formed, the material is prone to significant thermal shrinkage and structural collapse under thermal stress.
[0008] Traditional gas activation is limited by the problem of shallow surface activation: Traditional gas activation processes often occur after the independent carbonization stage. At this point, the pyrolyzed carbon material has undergone significant anisotropic shrinkage and densification, with severely contracted or even blocked internal mass transfer channels. This severely hinders the diffusion kinetics of the subsequent activation gas within the carbon matrix, limiting the gas-solid etching reaction to the material's surface region and making it difficult to achieve deep, uniform pore formation within the carbon framework. This phenomenon leads to spatial gradients in the pore structure and insufficient construction of through-hole rapid ion transport channels, preventing the effective formation of a highly active hierarchical porous structure with uniform distribution in three-dimensional space.
[0009] Existing porous carbon preparation methods generally suffer from the problem of "overdeveloped micropores and insufficient mesopores": although a higher specific surface area can provide more energy storage sites, an excessively high proportion of micropores will lead to difficulties in electrolyte wetting and increased resistance to ion diffusion; at the same time, due to insufficient connectivity between mesopores and macropores, ions are difficult to achieve rapid transport inside the electrode, especially under high-rate charge and discharge conditions, which can easily lead to severe concentration polarization and charge transport polarization, thereby limiting the capacity utilization and power performance improvement of hybrid capacitors.
[0010] To address the problems of structural collapse, uneven activation, and pore size mismatch in existing biomass porous carbon materials used in hybrid capacitor applications, this invention aims to solve the following technical problems: This study addresses the problems encountered during the pyrolysis and carbonization of biomass materials. These problems include thermal shrinkage, pore blockage, and structural collapse caused by the instability of the natural hydrogen bond network, volatilization, and framework rearrangement; as well as the obstruction of activation gas diffusion due to the shrinkage and densification of the carbon framework at high temperatures. Consequently, gas-solid phase etching is limited to the shallow outer layer, resulting in local overactivation while the interior remains unactivated. This leads to insufficient activation depth, only activating the material surface and making it difficult to effectively construct a uniform hierarchical porous structure.
[0011] This addresses the problems of slow electrolyte wetting, increased ion diffusion resistance, and limited rate performance caused by the excessively high proportion of micropores and insufficient mesopore connectivity in existing porous carbon materials.
[0012] Based on the above problems, how to pre-regulate the internal structure of biomass, reduce pyrolysis shrinkage, and construct internal mass transfer channels before high-temperature carbonization, so as to promote the subsequent vapor-phase etching to penetrate into the material and achieve uniform activation, has become an important research direction in the field of biomass-based hierarchical porous carbon materials. Summary of the Invention
[0013] In view of this, the present invention provides a hierarchical porous carbon material, its preparation method and application.
[0014] A method for preparing a hierarchical porous carbon material includes the following steps: (1) Crush the biomass raw materials and sieve them to obtain biomass powder with uniform particle size; (2) Soak the biomass powder obtained in step (1) in a mixed solution containing a swelling agent while stirring, and then dry it; (3) Add a polycarboxylic acid crosslinking agent and a catalyst to the material obtained in step (2), and then perform low-temperature heat treatment to obtain the precursor; (4) The precursor obtained in step (3) is placed in an inert atmosphere for high-temperature carbonization, and after reaching the activation temperature, an activation gas is introduced for gas-solid phase etching to obtain carbon material. (5) Wash the carbon material obtained in step (4) and then dry it to obtain a graded porous carbon material.
[0015] Furthermore, in step (1), the biomass raw material is one or more of coconut shell, walnut shell, wood chip, straw, bamboo powder, fruit shell, fruit kernel or fir wood, and the sieved particle size is 40-200 mesh.
[0016] Furthermore, in step (2), the swelling agent is one or more of the following: a mixture of choline chloride and urea, a mixture of choline chloride and glycerol, urea, thiourea, ethanol, ethylene glycol, glycerol, zinc chloride, sulfuric acid, phosphoric acid, ferric chloride, or dimethyl sulfoxide. The amount of swelling agent added is 5%-40% of the biomass powder mass, and the solvent of the mixed solution containing the swelling agent is deionized water.
[0017] The beneficial effects of the above-mentioned further technical solutions are as follows: During the swelling process, the swelling agent can weaken the hydrogen bond interactions between cellulose, hemicellulose and lignin inside the biomass, promote the stretching of biomass molecular chains and structural expansion, thereby increasing the openness of natural vascular bundles and cell wall pores; after swelling treatment, a looser and more continuous mass transfer network is formed inside the biomass, providing an effective transport path for the subsequent diffusion of activation gas into the carbon skeleton and uniform gas-solid phase etching.
[0018] Furthermore, in step (2), the stirring speed is 300-500 rpm, the soaking temperature is 40-90℃, the soaking time is 2-24 h, the drying temperature is 60-100 ℃, and the drying time is 12-24 h.
[0019] Furthermore, in step (3), the polycarboxylic acid is one or more of citric acid, tartaric acid, malic acid, oxalic acid or phytic acid; The catalyst is one or more of sodium hypophosphite (SHP), phosphate, or phosphite.
[0020] The amount of the added polycarboxylic acid is 2%-30% of the biomass powder mass.
[0021] The catalyst addition amount is 1%-20% of the mass of the polycarboxylic acid.
[0022] Furthermore, in step (3), the low-temperature heat treatment temperature is 120-200℃, preferably 130-160℃, the heat treatment time is 1-6 h, and the treatment atmosphere is air.
[0023] The beneficial effects of the above-mentioned further technical solution are as follows: In the low-temperature heat treatment stage, the core function of the catalyst is to reduce the activation energy of the reaction, thereby achieving rapid low-temperature shaping of the precursor. Under conditions of 130–160℃, the catalyst preferentially induces the rapid dehydration of adjacent carboxyl groups within the polycarboxylic acid molecule, generating a highly active cyclic anhydride intermediate. This intermediate then undergoes an esterification reaction with the free hydroxyl groups on the biomass macromolecular chain, constructing a stable cross-linked network between the biomass molecular chains, thereby improving the stability of the framework structure and inhibiting high-temperature pyrolysis shrinkage. This mechanism allows the cross-linking reaction to be completed rapidly before the biomass undergoes thermal shrinkage, constructing a rigid three-dimensional covalent support network within the framework. This network not only effectively fixes the mesoporous / macroporous channels formed in the early swelling stage, but also provides the material with key mechanical protection against structural collapse during subsequent high-temperature pyrolysis.
[0024] Furthermore, in step (4), the high-temperature carbonization temperature is 700-1000℃, the heating rate is 2-10℃ / min, the holding time is 1-5 h, and the inert atmosphere is nitrogen or argon. The activation start temperature is 700-950℃, and the activation time is 0.5-4 h; the activation gas includes one or more of CO2, water vapor or air, and the activation gas flow rate is 20-500 mL / min.
[0025] The beneficial effects of the above-mentioned further technical solutions are as follows: the esterification crosslinking network constructed in step (3) can improve the stability of the skeleton structure and reduce the structural densification caused by thermal decomposition shrinkage during the high-temperature carbonization process, thereby preserving the continuous mass transfer channels inside the biomass, promoting the diffusion of activated gas into the carbon skeleton, and realizing the construction of uniform gas-solid phase micro-etching and hierarchical pore structure.
[0026] Macropores originate from the structure of natural biomass; mesopores originate from swelling and pore expansion; micropores originate from gas micro-etching; post-processing does not require extensive acid washing.
[0027] Furthermore, in step (5), the washing is water washing, the drying temperature is 60-120℃, and the drying time is 6-24 h.
[0028] The present invention also provides a hierarchical porous carbon material prepared by the preparation method described above.
[0029] The present invention also provides an application of the hierarchical porous carbon material as a negative electrode in a sodium-ion hybrid capacitor.
[0030] This invention does not rely on traditional strong chemical activation to achieve ultra-high specific surface area, but proposes a synergistic construction strategy of "pre-structure regulation-assisted gas-phase internal etching". By pre-opening the internal mass transfer channels of biomass through pre-physical swelling, and using low-temperature cross-linking and curing to stabilize and constrain the expanded framework structure, the activation gas can penetrate deep into the carbon framework to perform uniform gas-solid phase micro-etching during the subsequent high-temperature gas-phase activation process. This avoids the problem that traditional gas activation only occurs on the surface of the material, and finally constructs a porous carbon material with a through-type hierarchical structure of "micropores-mesopores-macropores".
[0031] The core mechanism is as follows: First, the dense hydrogen bond network inside the biomass is destroyed by pre-physical swelling and the natural vascular bundle channels are opened; then, the expanded skeleton structure is stabilized by low-temperature cross-linking and curing to suppress skeleton shrinkage, structural densification and pore blockage during high-temperature pyrolysis; under this premise, high-temperature vapor etching can penetrate deep into the material and achieve uniform micropore development, thereby forming a through-type hierarchical pore structure and improving ion diffusion kinetics.
[0032] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a synergistic construction strategy of "pre-structural stabilization assisting internal vapor-phase etching" to achieve coordinated regulation of biomass pyrolysis shrinkage behavior, internal mass transfer pathways, and gas-solid phase activation processes. This effectively suppresses structural densification and pore collapse during high-temperature pyrolysis, promotes uniform diffusion and etching of activation gas into the carbon framework, and ultimately constructs a hierarchical pore structure with continuous ion transport channels. Compared to existing technologies, this invention has the following advantages: 1. Activation penetrates deep into the bulk phase of the material, resulting in high porosity. This invention opens the natural structure of biomass through pre-swelling and stabilizes and locks the expanded skeleton using low-temperature esterification crosslinking, effectively suppressing high-temperature pyrolysis volume shrinkage that leads to structural densification, while also avoiding pore blockage. A pre-constructed through-type internal mass transfer channel allows subsequent activation gas to penetrate deep into the carbon skeleton for uniform gas-solid phase micro-etching, effectively overcoming the limitations of traditional gas activation methods that restrict mass transfer to the material surface.
[0033] 2. Construct a hierarchical pore structure that spans from micropores to mesopores to macropores. Among them, macropores are beneficial for electrolyte storage; mesopores are beneficial for rapid ion transport; and micropores are beneficial for providing energy storage sites; thus achieving a synergistic improvement in energy storage capacity and kinetic performance.
[0034] 3. The process is green, the post-processing is simple, and it is suitable for large-scale production. This invention eliminates the need for large amounts of highly corrosive activators, and post-treatment can be completed with simple water washing, effectively reducing equipment corrosion, waste liquid discharge, and production costs, making it more suitable for industrial continuous production. Attached Figure Description
[0035] Figure 1 This is a morphology diagram of the hierarchical porous carbon material in Example 1. Detailed Implementation
[0036] The present invention will be further described below with reference to embodiments and comparative examples. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. All equivalent substitutions, conventional adjustments or improvements made based on the technical concept of the present invention should fall within the scope of protection of the present invention.
[0037] Example 1 A method for preparing a hierarchical porous carbon electrode includes the following steps: (1) Preparation of biomass porous carbon materials: Coconut shell raw material is crushed and sieved through 100 mesh to obtain coconut powder raw material.
[0038] (2) The sieved coconut powder from step (1) was soaked in an aqueous solution of choline chloride-urea eutectic solvent, wherein the eutectic solvent was prepared by mixing choline chloride and urea at a molar ratio of 1:2, the mass concentration of the eutectic solvent was 10 wt%, and the solid-liquid ratio was 1:10 (g:mL), and the soaking was carried out at 60 ℃ and 500 r / min for 2 h. The soaked coconut powder was then centrifuged and dried at 80 ℃ for 12 h.
[0039] (3) Add 20% of the mass of coconut powder, citric acid and 5% of the mass of citric acid, sodium hypophosphite crosslinking solution to the material obtained in step (2). Then, dry the impregnated material at 80°C and heat it to 160°C at 2°C / min in air atmosphere and keep it at that temperature for 3 hours to complete the low-temperature crosslinking curing.
[0040] (4) The precursor obtained in step (3) was heated to 850°C at 5°C / min under a nitrogen atmosphere and held for 1 h. Then the CO2 atmosphere was switched at a flow rate of 100 mL / min and held for another 1 h for vapor phase etching.
[0041] (5) Wash the material obtained in step (4) with water until it is neutral, and dry it at 80°C for 12 h to obtain the final graded porous carbon material.
[0042] A porous carbon material, conductive agent, and binder were mixed uniformly at a mass ratio of 8:1:1 to prepare a negative electrode slurry, which was then coated onto the surface of a copper foil current collector. After drying and rolling, the slurry was stamped to serve as the negative electrode. The porous carbon negative electrode was then matched and assembled with a commercial activated carbon positive electrode to construct a sodium-ion hybrid capacitor full cell. The negative electrode material was pre-intercalated with sodium and then matched and assembled with the activated carbon positive electrode at a mass ratio of 1:2-1:4. A glass fiber membrane was used as the separator, and 1 mol / L NaClO4 dissolved in an EC / DEC (volume ratio 1:1) mixed solution was used as the electrolyte. A CR2032 type sodium-ion hybrid capacitor was assembled in a high-purity argon atmosphere glove box. The electrochemical performance of the assembled sodium-ion hybrid capacitor was tested, with the following parameters: test voltage range 1.0-4.0 V; current density 0.1-20 A / g. Further testing methods such as constant current charge-discharge, cyclic voltammetry, and AC impedance were used to evaluate the specific capacitance, energy density, power density, rate performance, and cycle stability of the device.
[0043] Example 2 A method for preparing a hierarchical porous carbon electrode includes the following steps: (1) Preparation of biomass porous carbon materials: Coconut shell raw material is crushed and sieved through 100 mesh to obtain coconut powder raw material.
[0044] (2) Soak the sieved coconut powder from step (1) in a urea solution containing 10% of the coconut powder mass, stir at 500 rpm, heat in a water bath to 80°C, and maintain for 2 hours. Then, centrifuge the soaked coconut powder to dry it, and dry it at 80°C for 12 hours.
[0045] (3) Add 20% phytic acid solution to the material obtained in step (2), then dry the impregnated material at 80°C, and heat it to 160°C at 2°C / min in air atmosphere and keep it at that temperature for 3 hours to complete the low-temperature crosslinking curing.
[0046] (4) The precursor obtained in step (3) was heated to 850°C at a rate of 5°C / min under a nitrogen atmosphere and held for 1 h. Then the CO2 atmosphere was switched at a flow rate of 100 mL / min and held for another 1 h for vapor phase etching. (5) Wash the material obtained in step (4) with water until it is neutral, and dry it at 80°C for 12 h to obtain the final graded porous carbon material.
[0047] The sodium-ion capacitor was assembled in the same manner as in Example 1. Comparative Example 1 (1) Preparation of biomass porous carbon materials: Coconut shell raw material is crushed and sieved through 100 mesh to obtain coconut powder raw material.
[0048] (2) Add 20% of the mass of coconut powder, citric acid and 5% of the mass of citric acid, sodium hypophosphite crosslinking solution to the material obtained in step (1). Then, dry the impregnated material at 80°C and heat it to 160°C at 2°C / min in air atmosphere and keep it at that temperature for 3 hours to complete the low-temperature crosslinking curing.
[0049] (3) The dried coconut powder from step (2) is heated to 900°C at 5°C / min under a nitrogen atmosphere and kept at that temperature for 2 hours.
[0050] (4) The precursor obtained in step (3) was heated to 850°C at 5°C / min under a nitrogen atmosphere and held for 1 h. Then the CO2 atmosphere was switched at a flow rate of 100 mL / min and held for another 1 h for vapor phase etching.
[0051] The sodium-ion capacitor was assembled in the same manner as in Example 1.
[0052] Comparative Example 2 (1) Preparation of biomass porous carbon materials: Coconut shell raw material is crushed and sieved through 100 mesh to obtain coconut powder raw material.
[0053] (2) Soak the sieved coconut powder from step (1) in 10% choline chloride-urea solution containing 10% of the coconut powder mass, heat in a water bath to 80°C, and maintain for 2 hours. Then, centrifuge the soaked coconut powder to dry it, and dry it at 80°C for 12 hours.
[0054] (3) The dried coconut powder from step (2) is heated to 900°C at 5°C / min under a nitrogen atmosphere and kept at that temperature for 2 hours.
[0055] (4) The precursor obtained in step (3) was heated to 850°C at 5°C / min under a nitrogen atmosphere and held for 1 h. Then the CO2 atmosphere was switched at a flow rate of 100 mL / min and held for another 1 h for vapor phase etching.
[0056] The sodium-ion capacitor was assembled in the same manner as in Example 1. Comparative Example 3 (1) Preparation of biomass porous carbon materials: Coconut shell raw material is crushed and sieved through 100 mesh to obtain coconut powder raw material.
[0057] (2) Soak the sieved coconut powder from step (1) in 10% choline chloride-urea solution containing 10% of the coconut powder mass, heat in a water bath to 80°C, and maintain for 2 hours. Then, centrifuge the soaked coconut powder to dry it, and dry it at 80°C for 12 hours.
[0058] (3) Add 20% of the mass of coconut powder, citric acid and 5% of the mass of citric acid, sodium hypophosphite crosslinking solution to the material obtained in step (2). Then, dry the impregnated material at 80°C and heat it to 160°C at 2°C / min in air atmosphere and keep it at that temperature for 3 hours to complete the low-temperature crosslinking curing.
[0059] (4) The precursor obtained in step (3) is heated to 850°C at 5°C / min under a nitrogen atmosphere and kept at that temperature for 2 hours.
[0060] (5) Wash the material obtained in step (4) with water until it is neutral, and dry it at 80°C for 12 h to obtain the final graded porous carbon material.
[0061] The sodium-ion capacitor was assembled in the same manner as in Example 1. Experimental data Table 1 Structural Parameters
[0062] Table 2. Full Cell Performance of Hybrid Capacitors
[0063] Analysis of experimental results: A comparison of Example 1 and Comparative Example 1 shows that: Without the swelling step, the gas cannot penetrate deep into the material and can only perform limited etching on the surface. As a result, the resulting pore structure is uneven, the proportion of mesopores is significantly reduced, and the rate performance is significantly decreased.
[0064] A comparison between Example 1 and Comparative Example 2 shows that: If low-temperature cross-linking and curing is not carried out, the natural pores that open after swelling will re-close during high-temperature pyrolysis, causing significant thermal shrinkage of the material, ultimately resulting in pore structure collapse and a decrease in ion diffusion capacity.
[0065] A comparison between Example 1 and Comparative Example 3 shows that: Although low-temperature crosslinking can effectively maintain the natural structure, if subsequent CO2 vapor phase etching is lacking, the micropore development will be insufficient, the specific surface area will be significantly lower, and the energy storage capacity will be limited.
[0066] As shown in Tables 1 and 2, this invention achieves the construction of a through-type hierarchical pore structure by employing a synergistic control mechanism of "pre-physical swelling—low-temperature cross-linking and curing—high-temperature vapor phase etching," while maintaining the integrity of the natural biomass framework. Specifically, macropores facilitate electrolyte storage; mesopores facilitate rapid ion transport; and micropores provide energy storage sites. Ultimately, this significantly improves the rate performance, cycle stability, and overall kinetic performance of the sodium-ion hybrid capacitor.
[0067] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a hierarchical porous carbon material, characterized in that, Includes the following steps: (1) Crush the biomass raw materials and sieve them to obtain biomass powder with uniform particle size; (2) Soak the biomass powder obtained in step (1) in a mixed solution containing a swelling agent while stirring, and then dry it; (3) Add a polycarboxylic acid crosslinking agent and a catalyst to the material obtained in step (2), and then perform low-temperature heat treatment to obtain the precursor; (4) The precursor obtained in step (3) is placed in an inert atmosphere for high-temperature carbonization, and after reaching the activation temperature, an activation gas is introduced for gas-solid phase etching to obtain carbon material. (5) Wash the carbon material obtained in step (4) and then dry it to obtain a graded porous carbon material.
2. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (1), the biomass raw material is one or more of coconut shell, walnut shell, wood chip, straw, bamboo powder, fruit shell, fruit kernel or fir wood, and the sieve particle size is 40-200 mesh.
3. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (2), the swelling agent is one or more of the following: a mixture of choline chloride and urea, a mixture of choline chloride and glycerol, urea, thiourea, ethanol, ethylene glycol, glycerol, zinc chloride, sulfuric acid, phosphoric acid, ferric chloride, or dimethyl sulfoxide. The amount of swelling agent added is 5%-40% of the biomass powder mass, and the solvent of the mixed solution containing the swelling agent is deionized water.
4. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (2), the stirring speed is 300-500 rpm, the soaking temperature is 40-90℃, and the soaking time is 2-24 h; the drying temperature is 60-100 ℃, and the drying time is 12-24 h.
5. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (3), the polycarboxylic acid is one or more of citric acid, tartaric acid, malic acid, oxalic acid or phytic acid; The catalyst is one or more of sodium hypophosphite (SHP), phosphate, or phosphite. The amount of the added polycarboxylic acid is 2%-30% of the biomass powder mass. The catalyst addition amount is 1%-20% of the mass of the polycarboxylic acid.
6. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (3), the low-temperature heat treatment temperature is 120-200℃, the heat treatment time is 1-6 h, and the treatment atmosphere is air.
7. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (4), the high-temperature carbonization temperature is 700-1000℃, the heating rate is 2-10℃ / min, the holding time is 1-5 h, and the inert atmosphere is nitrogen or argon. The activation start temperature is 700-950℃, and the activation time is 0.5-4 h; the activation gas includes one or more of CO2, water vapor or air, and the activation gas flow rate is 20-500 mL / min.
8. The method for preparing a hierarchical porous carbon material according to claim 1, characterized in that, In step (5), the washing is water washing, the drying temperature is 60-120℃, and the drying time is 6-24 h.
9. A hierarchical porous carbon material prepared by the preparation method according to any one of claims 1-8.
10. The application of the hierarchical porous carbon material of claim 9 as a negative electrode in a sodium-ion hybrid capacitor.